Cell cycle related proteins as prognostic parameters in radically resected non-small cell lung cancer. Issue 7 (23rd June 2005) - Esposito, V; Baldi, A; De Luca, A; Tonini, G; Vincenzi, B; Santini, D; Persichetti, P; Mancini, A; Citro, G; Baldi, F; Groeger, A M; Caputi, M
Abstract : Background: Experimental evidence suggests that lung cancer development and progression can be linked to an increased proliferation rate. Aims/Methods: To evaluate the immunohistochemical expression of seven components of the cell cycle machinery in a series of well characterised non-small cell lung cancer (NSCLC) specimens (n  =  105). Results: Multivariate analysis revealed that simultaneous loss of expression of three of these factors—cyclin D1, the cyclin dependent kinase inhibitor p16, and the tumour suppressor retinoblastoma protein Rb2/p130—correlated with survival, confirming the hypothesis that the cyclin D1–p16–retinoblastoma tumour suppressor pathway is inactivated in most lung cancer samples. Conclusions: These results suggest that loss of control of cell cycle checkpoints is a common occurrence in lung cancer and support the idea that functional cooperation between different cell cycle regulatory proteins constitutes another level of regulation in cell growth control and tumour suppression.